2006
DOI: 10.1128/jvi.00187-06
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis and Organization of theNeodiprion abietisNucleopolyhedrovirus Genome

Abstract: Of 30 baculovirus genomes that have been sequenced to date, the only nonlepidopteran baculoviruses include the dipteran Culex nigripalpus nucleopolyhedrovirus and two hymenopteran nucleopolyhedroviruses that infect the sawflies Neodiprion lecontei (NeleNPV) and Neodiprion sertifer (NeseNPV). This study provides a complete sequence and genome analysis of the nucleopolyhedrovirus that infects the balsam fir sawfly Neodiprion abietis (Hymenoptera, Symphyta, Diprionidae). The N. abietis nucleopolyhedrovirus (NeabN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 108 publications
1
33
0
Order By: Relevance
“…Although still distantly, gammabaculoviruses are thought to be more closely related than deltabaculoviruses to alphabaculoviruses and betabaculoviruses [3]. However, gammabaculoviruses appear to lack an envelope fusion protein homolog [22,28,31] and, as a consequence, lack a budded virus (BV) phenotype common to the other three genera. Group I alphabaculoviruses, such as that of Autographa californica (AcMNPV), encode GP-64 [32] whereas group II NPVs, for example, Lymantria dispar LdMNPV, encode F-protein [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although still distantly, gammabaculoviruses are thought to be more closely related than deltabaculoviruses to alphabaculoviruses and betabaculoviruses [3]. However, gammabaculoviruses appear to lack an envelope fusion protein homolog [22,28,31] and, as a consequence, lack a budded virus (BV) phenotype common to the other three genera. Group I alphabaculoviruses, such as that of Autographa californica (AcMNPV), encode GP-64 [32] whereas group II NPVs, for example, Lymantria dispar LdMNPV, encode F-protein [33].…”
Section: Discussionmentioning
confidence: 99%
“…Unprecedented outbreaks of balsam fir sawfly populations on the island of Newfoundland (Newfoundland and Labrador (NL), Canada) [17] have led to the development, registration, commercialization, and use Psyche of an N. abietis-specific Gammabaculovirus (NeabNPV) [18][19][20][21]. The genome of NeabNPV has been sequenced [22], and the in vivo replication and transcription kinetics studied [23]. There is, however, a dearth of information on the pathology of sawfly NPVs in the literature, although they are thought to only infect the midgut epithelium of their hosts [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Progeny virions were occluded directly without the production of BVs (reviewed in Federici, 1997;Slack & Arif, 2007;Rohrmann, 2011). Sequence data from gammabaculoviruses failed to identify homologues to the alphabaculovirus fusion proteins, GP64 or F-protein (Duffy et al, 2006;Lauzon et al, 2006), indicating the absence of the BV phenotype. Also lacking in gammabaculoviruses are viral fibroblast growth factor (vfgf) homologues (Jehle et al, 2006), that have been shown to accelerate the establishment of systemic infections in alphabaculoviruses (Detvisitsakun et al, 2007;Passarelli, 2011).…”
Section: Disease Progression In Gammabaculovirusesmentioning
confidence: 99%
“…In mosquito hosts, following the primary infection of the gastric caeca and posterior midgut by ODVs, deltabaculovirus BVs also spread the infection further from cell to cell but only to these same tissues (Moser et al, 2001). Sawfly gammabaculoviruses do not appear to have a BV phenotype (Duffy et al, 2006;Garcia-Maruniak et al, 2004;Lauzon et al, 2004) and OBs are only produced in the nuclei of midgut epithelial cells (Federici, 1997).…”
Section: Classification and Origins Of Baculovirusesmentioning
confidence: 99%
See 1 more Smart Citation